Strategy of Social Fund Distribution in ACT-MRI Parepare - Muhammad Majdy Amiruddin; Islamul Haq; Nur Alviana Nasir; Nur hasana (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to analyze the philanthropic fund allocation strategy implemented by the Aksi Cepat Tanggap with the Masyarakat Relawan Indonesia (ACT-MRI) of Parepare. The approach in this research is a qualitative approach with a case study research design. The results showed that philanthropic funds collected by MRI of Parepare City would be distributed into four main programs, intense programs, compensation for the poor of the MSR system (Mobile System Resecue), assistance in the goods to money transformation and Direct Delivery of aid funds to recipients. The distribution adapted diversivication strategy. This research is expected to be a reference to the management and volunteers to improve cooperation with the government and educational institutions. Cooperation with the government is needed so that the intense program and MSR can run more optimally without overlapping interests. Educational institutions can make a contribution in the form of volunteers so that human resources can be guaranteed